Radiiation exposure and food safety - Slobodyan, Olga; Neshchadym, Larisa; Zaets, Vira (My University, 2016)
Food irradiation is a technology that improves the safety and extends the shelf life of food by reducing or eliminating microorganisms and insects. Preservation-irradiation can be used to destroy or inactivated organisms that cause spoilage and decomposition and extend the shelf life of food.
Keywords: кафедра екології та екоменеджменту; радіоактивність; поглинута доза; захист від радіації; радиоактивность; защита от радиации; radiation; absorbed dose; radiation protection